Spring Water Catchment Building and Water Distribution System for Domestic Needs - Achmad Yopi Suyitno Pribawanto; Nora Herdiana Pandjaitan; Sutoyo Sutoyo (The University of Lampung, 2024)
The population growth implies that the population's need for clean water tend to increase. Clean water availability is not optimal due to geographical factors and discharge reductions during dry season. This research was conducted to design spring water catchment building and water distribution system at Kalikajar Village, Wonosobo. The population data, water demand, and spring discharge were utilized in this research. The population growth was calculated with arithmetic, geometric, exponential, and logistic method. Then water demand was calculated based on SNI 19-6728.1-2002. The population growth which predictably reaches 5328 people in 2050 will result in increasing clean water demand by 9.68% with domestic water demand of 4.63 L/s. The spring discharge measured at the research location showed an average of 10.80 L/s. Therefore, the spring discharge is able to meet the population needs in the projected year. The spring catchment building was designed with Type B, while three reservoir were designed with the capacity of 7 m3 each. The water distribution is designed with gravity system because the elevation difference between the spring and the village is more than 10 m. The PVC pipeline used diameter of 100 – 150 mm, with total length of 11843 m. The design meets the calculated requirement and could be implemented. Keywords: Distribution system, Reservoir, Spring water, Hilly areas, Water consumption